Solution‐Processable Donor‐Acceptor‐Donor Oligomers with Cross‐Linkable Functionality. Issue 5 (18th December 2014) - Brotas, Graça; Costa, Cristiana; Dias, Sandra I. G.; Costa, Pedro M. M.; Di Paolo, Roberto E.; Martins, João; Farinhas, Joana; Alcácer, Luís; Morgado, Jorge; Matos, Manuel; Charas, Ana
<x xml:space="preserve">Abstract</x> Electron‐acceptor units, combined with bithiophene substituted with flexible chains end‐functionalized with cross‐linkable moieties, provide soluble donor‐acceptor‐donor (DAD) π‐conjugated oligomer‐type molecules with cross‐linking ability and broad absorption in the visible spectrum. A study on the cross‐linking conditions of the new oligomers to yield insoluble polymer networks is presented, including conditions for obtaining polymer films over poly(3, 4‐ethylenedioxythiophene):polystyrene sulfonate‐covered substrates. The combination of the DAD molecular design and cross‐linking functionality opens prospects for applications in solution‐processed small‐molecule solar cells with morphologically‐stable organic layers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>